(3TQM JgPjH GdCUhds - (3MSjf GdYejOj GdfLajs
(3ChdgG (B:s
... (3bGd bOS Gddg QhMg (B: (3hXfjI GdWQjb dG JfGajg YedjI GdMce , Cbhd (B: (3gPG LhGH SDGd ebOQ jQO Ydi MO Gdabg GdePchQ hJbQjQ GdSDGd Cf jchf Gdabg ef HGH GdXfhf (B..s
(3BNQgG (B:s
.. (3hjQi GLJeGY GdfGS Ydjg hGdYed HaJhGg hGdGfbjGO Edi bhdg hGdYed HebJVGg hGbHGd GdeSdejf Ydi SDGdg hGSJQTGOg hJYXjeg hEcQGeg hdG jLhR ddYGej JbdjO ef jXfg NGdjG ef GdYde (B..s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3CUhd Gdabgs